The genetics of hyper IgE syndromes - AlYafie, Randa; Velayutham, Dinesh; van Panhuys, Nicholas; Jithesh, Puthen Veettil (Frontiers in Immunology, 2025)
Hyper IgE syndromes (HIES) form a rare group of primary immunodeficiency disorders (PIDs) distinguished by persistent skin abscesses, dermatitis, allergies, and infections, in addition to their characteristic high serum IgE levels. Autosomal dominant (AD) and autosomal recessive (AR) genetic defects have been reported in HIES. From a clinical perspective, AD-HIES cases generally exhibit several non-immunologic features, including connective tissue, dental and skeletal abnormalities, whilst AR-HIES conditions have a higher incidence of neurologic complications and cutaneous viral infections. Genetic defects associated with HIES lead to impaired immune signaling, affecting pathways crucial for immune cell development, function, and immune response to pathogens/allergens. As a result, HIES patients are predisposed to recurrent bacterial and/or fungal infections, as well as atopic allergic responses. In many cases, the exact biological mechanisms responsible for the variations observed in the clinical phenotypes between the two inherited forms of HIES are still unclear. In this review, we describe the genetic basis of HIES with a distinction between the AR-HIES and AD-HIES forms, to better comprehend the different underlying molecular mechanisms, a distinction which is imperative for the accurate diagnosis, management, and development of targeted therapies for HIES patients.